THE INVESTIGATION OF FACTORS INFLUENCING THE SERVICE QUALITY OF STARBUCKS COFFEE AND CUSTOMERS' INTENTION TO SUSTAIN CONSUMPTION - Wu Qianying; Mohammad Ismail; Syarizal Abdul Rahim, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
As the food and beverage industry experiences rapid growth, competition becomes increasingly intense, high service quality becomes the key factor to win the competitive advantage. By providing excellent service quality, the company ensures the highest level of customer satisfaction and builds solid customer loyalty, which becomes vital for their survival. The purpose of this study is to explore the impact of service quality on customer satisfaction and loyalty and take Starbucks China as a case study. Specifically, we will focus on analyzing the impact of Starbucks coffee service quality on customer satisfaction and loyalty. A quantitative method was adopted in this study, and a questionnaire was used to collect data. The items used in the questionnaire were developed according to the existing scale. In this study, data were collected from 294 Starbucks customers in Guangzhou, and a total of 500 questionnaires were sent out. During the process of data screening and cleaning, 467 questionnaires were generated, which were analyzed using the Social Science Statistical package (SPSS). In this paper, structural equation modeling (SEM) is used to analyze the data, in which a two-step approach is used to evaluate the measurement model and the structural model.